Pulmonary thromboembolism and sudden death in psychiatric patients – Two cases report - Marinković, Nadica Spasoje; Rančić, Dragana (Vojnosanitetski pregled, 2017)
Introduction. Pulmonary thromboembolism occurs usually by running a thrombus from the deep veins of the legs rarely periprostatic or periuteric veins. Virchow’s triad of necessary conditions for the occurrence of thrombosis involves disruption of blood flow, disruption of blood chemistry and damage to the vessel wall. Venous thrombosis is often associated with the implementation of antipsychotic therapy. Case report. We reported two cases of sudden death of psychiatric patients who were in both cases fixed during hospitalization. The first case was a 26-year-old woman treated a year with the diagnose of postpartum reactive psychosis. She was hospitalized because of mental state worsening with a dominant depressed mood, visual and auditory hallucinations. Her therapy was determined by diazepam, clozapine, haloperidol and lamotrigine. Suddenly, the patient died on the fifth day of hospitalization. The autopsy showed massive thromboembolism of the pulmonary artery branches. Toxicological analysis revealed the presence of therapeutic doses of antipsychotics. The second case was a-45-year-old men, a long-time alcoholic. On admission, the diagnosis of delirium tremens was established, and diazepam and haloperidol were administered. On the fifth day of hospitalization, he suddenly died. The autopsy showed thromboembolism of the branch of the pulmonary artery. Toxicological analysis established the presence of nordiazepam in urine (0.06 mg/L). Both patients were fixed during hospitalization. Conclusion. Both presented psychiatric patients were younger than 50 years, were not overweight, did not have changes of the venous blood vessels. Nowadays, when the issue of medical responsibility often arises in these and similar cases of sudden death in patients treated in psychiatric clinics, the questions on medical malpractice could be expected.